A promising common safe asset - European MBS: Conference summary and selected contributions - Robert Holzmann; Philipp Schnabl; David Marsh; Edward Golding; Jesper Berg; Markus Schwaiger; Luis Brandao Marques; Eleonora Endlich (Oesterreichische Nationalbank (OeNB), 2025)
In the USA, mortgage-backed securities (MBS) play an important role in monetary policy transmission, with the Federal Reserve and banks as major investors. Europe's MBS market is small by comparison. Could Europe benefit from a standardized and liquid MBS market similar to that in the USA? Could it help create a common safe asset and strengthen Europe's financial autonomy? On June 10, 2025, renowned experts discussed this and related questions at a conference hosted by the Oesterreichische Nationalbank (OeNB). This report provides a summary of the event and selected contributions.
Keywords: 330